TPACK Based: A Need Analysis for ELT Materials Development - Devi, Ravena; Ikhsanudin, Ikhsanudin (Universitas Lancang Kuning, 2023)
Maintaining current levels of knowledge necessitates putting learning into daily life. Currently, the development of technology and information has been very rapid, so it is possible to carry out technology-based learning. The term